PATH-36. GENOMIC MARKERS OF RECURRENCE RISK IN ATYPICAL MENINGIOMA FOLLOWING GROSS TOTAL RESECTION. (14th November 2022) - Vaubel, Rachael; Kumar, Rahul; Weiskittel, Taylor; Jenkins, Sarah; Dasari, Surendra; Uhm, Joon; Lachance, Daniel Honore; Brown, Paul; Van Gompel, Jamie; Kipp, Benjamin; Sukov, William; Giannini, Caterina; et al.
Abstract: Atypical meningiomas (CNS WHO grade 2) show an intermediate risk of recurrence/progression, and molecular parameters informing management following gross total resection (GTR) remain to be established. We performed comprehensive genomic analysis in 63 patients who underwent GTR of an atypical meningioma. Median age was 59.8 years, 41 patients (65.1%) were female, and 8/62 patients (12.9%) underwent radiation therapy following resection. Follow-up was available for all patients (median 10 years), with recurrence/progression in 17 (5-year PFS: 84.2%; 10-year PFS: 71.0%). Tumors were evaluated by next generation sequencing (n=61), chromosomal microarray (n=63), DNA methylation profiling (n=62), and H3K27me3 immunohistochemistry (n=62). Next generation sequencing using a CLIA-certified 50-gene Neuro-Oncology specific panel identified pathogenic alterations in NF2 (n=31; 50.8%), SMARCB1 (n=5; 8.2%), AKT1 (n=2; 3.3%), TERT (n=1, 1.6%), SMO (n=1), SUFU (n=1), TP53 (n=1), and PTEN (n=1). There was trend toward decreased PFS in patients with NF2 alterations (p=0.078) which was not statistically significant. Copy number variants (CNVs) were identified using OncoScan (ThermoFisher). The most frequent CNVs were loss -22 (n=45; 71.4%), -1p (n=30, 47.6%), -14 (n=21, 33.3%), -6q (n=18, 28.6%), -10q (n=15, 23.8%), -X (n=13, 20.6%), and -18 (n=11, 17.4%). CNVs associated with decreased PFS included -1p (p=0.015), -7p (p=0.007), -10q (p=0.0007), and -18 (p=0.0376). DNA methylation profiling was performed using the Illumina MethylationEPIC array (n=62) and evaluated using the DKFZ classifier (v12.3). Based on the highest score, tumors matched to benign (n=32; 51.6%) or intermediate (n=29; 46.7%) meningioma subclasses or showed non-contributory profiles (n=1; 1.6%). Methylation class (benign vs. intermediate) showed no association with PFS (p=0.96). H3K27 trimethylation (H3K27me3) was unequivocally lost in 4 (6.5%) tumors, which was insufficient for PFS analysis. Overall, our study supports CNV profiling of atypical meningiomas following GTR, which can be implemented using existing, clinically validated technologies. Molecular predictors could guide use of radiotherapy in these patients.